Descriptive Study Toward Psychological Factors Affecting Post-Severely Injuried Athletes To Regain Peak Performance - Aulia, Prima (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2021)
This research aims to find out the psychological factors that affect the athletes to regain their peak performance after severe injuries. This research’s result could became one of references in severe injury athlete’s treatment to repossess their peak performance. This study is expected could became the first research that lead to further research connecting psychological factors with other variables and for further period it is expected that this study could be continued with advanced research by adding psychological intervention based on prior finding.The determined subject's criteria in this study are athletes who are encountering or have encountered severe injury since severe injury requires more than a month for recovery. Data collection's method that is been utilized is open questionnaire regarding the theme. Data analysis in this research is factor analysis. The factor analysis is utilized to reveal psychological factors emerging in its impact toward the post-severely injured athletes to regain peak performance.After conducting factor analysis, it found that psychological factors affecting the athletes returning to their peak performance after encountering severe injury are self-confident factors, training seriousness factor, following the trainer's advice factor, place/time disoriented factor, and focus faktor